Strengthening the National Human Rights Commission of Bangladesh through a Legislative Amendment to Fulfill its Commitments Under Sustainable Development Goals (SDGs) (Dhaka University Law Journal, 2021)
Abstract not availableDhaka University Law Journal, Vol. 31, 2020 P.143-174